2000
DOI: 10.1128/jb.182.20.5911-5915.2000
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Expression of a Thermus thermophilus Arginine Cluster: Presence of Unidentified Open Reading Frames and Absence of a Shine-Dalgarno Sequence

Abstract: A group of genes regulated by arginine was found clustered in the order argF-ORF1-argC-argJ-ORF4 between other, as yet uncharacterized, open reading frames (ORFs). Transcription starts were identified immediately upstream from argF and ORF4. Arginine repressed transcription that was initiated at argF but induced transcription of ORF4. The functions of ORF1 and ORF4 are unknown, but analysis of the sequence of ORF4 suggests that it is a membrane protein, possibly involved in transport of arginine or a related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The P arg promoter of T. thermophilus was previously shown to be inducible by arginine at the transcriptional level (Sanchez et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P arg promoter of T. thermophilus was previously shown to be inducible by arginine at the transcriptional level (Sanchez et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1978). Arginine and uracil‐free liquid medium with 20 mmol l −1 pyruvate as the carbon source and 10 mmol l −1 ammonium sulphate as the nitrogen source (Sanchez et al. 2000) was used for arginine induction experiments.…”
Section: Growth Conditionsmentioning
confidence: 99%
“…This region has been referred to as the downstream box (DB) (Sprengart et al ., 1996) or the downstream region (DR) (Stenström et al ., 2001a). Several suggestions have been presented as explanations to effects by this region, such as codon usage (Robinson et al ., 1984; Bulmer, 1988; Sorensen et al ., 1989), involvement in secondary structures (de Smit and van Duin, 1994), mRNA stability (Kuroda and Maliga, 2001), peptidyl‐tRNA drop‐off (Karimi and Ehrenberg, 1994; Dincbas et al ., 1999) or complementary binding to the 16S rRNA (Sprengart et al ., 1990; Faxen et al ., 1991; Hartz et al ., 1991; Etchegaray and Inouye, 1999; Sanchez et al ., 2000). However, the last suggestion appears to be experimentally refuted (Resch et al ., 1996; Blasi et al ., 1999; O’Connor et al ., 1999; La Teana et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For T. thermophilus, Sanchez et al (2000) previously suggested that the argF promoter is regulated by ArgR. For the initial investigation, we aligned the sequences between the argF promoter region containing the ARG box and the hcs promoter region (Fig.…”
Section: Identification Of Ttc1194 As the Argr Gene Of T Thermophilusmentioning
confidence: 99%